2009
DOI: 10.1074/jbc.m109.009738
|View full text |Cite|
|
Sign up to set email alerts
|

Phosphorylation of Williams Syndrome Transcription Factor by MAPK Induces a Switching between Two Distinct Chromatin Remodeling Complexes

Abstract: Changes in the environment of a cell precipitate extracellular signals and sequential cascades of protein modification and elicit nuclear transcriptional responses. However, the functional links between intracellular signaling-dependent gene regulation and epigenetic regulation by chromatin-modifying proteins within the nucleus are largely unknown. Here, we describe novel epigenetic regulation by MAPK cascades that modulate formation of an ATPdependent chromatin remodeling complex, WINAC (WSTF Including Nucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…The WSTF protein has recently been shown to be a target of MAP kinases both in vitro and in vivo (Oya et al 2009). MAPK phosphorylates WSTF protein within the WAC domain at serine 158 (S158).…”
Section: Post-translational Modifications Of Wstfmentioning
confidence: 99%
See 2 more Smart Citations
“…The WSTF protein has recently been shown to be a target of MAP kinases both in vitro and in vivo (Oya et al 2009). MAPK phosphorylates WSTF protein within the WAC domain at serine 158 (S158).…”
Section: Post-translational Modifications Of Wstfmentioning
confidence: 99%
“…While WSTF exists in both the phosphorylated and unphosphorylated form in vivo , researchers have shown that an unphosphorylatable WSTF mutant (WSTF S158A) displays a significantly reduced affinity for other components of the WINAC chromatin remodeling complex. This mutation also results in reduced WINAC transactivation and repression activity in the breast cancer cell line MCF7 (Oya et al 2009). Interestingly, WSTF S158A does not disrupt the association with ISWI and appears not to alter survival of cultured mouse embryonic fibroblast (MEF) cells upon treatment with MMS.…”
Section: Post-translational Modifications Of Wstfmentioning
confidence: 99%
See 1 more Smart Citation
“…5.2; Becker & Workman, 2013). Complexes in the SWI/SNF family include the large multisubunit BAF, PBAF, and WINAC complexes which function as coregulators of transcription, and they also aid in the repair of DNA damage (Oya et al, 2009; Wang et al, 1996). Remodeling reactions catalyzed by SWI/SNF family members include simple nucleosome sliding reactions, but they can include more dramatic reactions like creating DNA loops on the surface of nucleosomes or the eviction of H2A/H2B dimers from the nucleosome structure (Bowman, 2010).…”
Section: Atp-dependent Chromatin Remodelingmentioning
confidence: 99%
“…However, the most common cancer-related changes in the SWI/SNF complex are the loss or inactivation of the BRG1 or BRM subunit, which occur in a variety of tumors, including breast cancer[80],[81]. The genetic or epigenetic silencing of the BRG1 subunit is of particular relevance considering that, in addition to the BAF/PBAF complexes, BRG1 is the pivotal component in several other chromatin-remodeling and histone-modifying enzyme complexes, including the Williams syndrome transcription factor (WSTF)-including nucleosome assembly complex (WINAC), N-CoR, nucleosomal methylation activation complex (NUMAC), and mSin3A/histone deacetylase (HDAC) complex[82][84] ( Figure 3 ). In particular, when associated with coactivator-associated arginine methyltransferase-1 (CARM1) to form the NUMAC complex, BRG1 can recruit nuclear hormone receptors to EREs and cooperatively activate estrogen-dependent gene transcription[85][87].…”
Section: Maintenance Proteinsmentioning
confidence: 99%